Theoretical Investigation of PAHs: Implications to Diffuse Interstellar Bands. Issue Volume 9:Issue S297(2013) (21st February 2014) - Pathak, A.; Buragohain, M.; Hammonds, M.; Sarre, P. J.
Abstract: About a thousand optical absorption features on the interstellar extinction curve popularly known as the Diffuse Interstellar Bands (DIBs) have been observed. The numbers are increasing every year, thanks to the improvement in telescope and spectroscopic technology. Ultra-high resolution spectroscopic observations and emission features corresponding to some of the DIBs suggest that, some if not all, of these features are due to large molecules. The strength of DIBs depend on the amount of reddening which is directly proportional to the amount of material present between the background star and the observer. Since, the strengths of the DIBs are not strongly correlated with each other, there must be several carriers. Time Dependent Density Functional Theory (TDDFT) calculations are useful in narrowing down molecular systems that may be further investigated in the laboratory. The observations of the unidentified infrared (UIR) bands point towards the widespread presence of Polycyclic Aromatic Hydrocarbon (PAH) molecules. Though, not a single PAH has been discovered in interstellar space, these are the largest molecules suspected to be present. PAHs are stable towards energetic environment prevailing under interstellar conditions rendering these molecules to be good candidates as DIB carriers. We report TDDFT calculations to predict electronic transitions of neutral, protonated-deuteronated and PAHs with five member rings with various sites of protonation and deuteronation. Compared to their neutral forms, these charged isoelectronic forms of PAHs are predicted to have active transitions in the visible region, which means they are suitable candidates as carriers for some of the DIBs and laboratory studies are warranted for these systems.